2007
DOI: 10.1074/jbc.m707165200
|View full text |Cite
|
Sign up to set email alerts
|

The Serine Protease Domain of Hepatitis C Viral NS3 Activates RNA Helicase Activity by Promoting the Binding of RNA Substrate

Abstract: Nonstructural (NS) protein 3 is a DEXH/D-box motor protein that is an essential component of the hepatitis C viral (HCV)replicative complex. The full-length NS3 protein contains two functional modules, both of which are essential in the life cycle of HCV: a serine protease domain at the N terminus and an ATPase/helicase domain (NS3hel) at the C terminus. Truncated NS3hel constructs have been studied extensively; the ATPase, nucleic acid binding, and helicase activities have been examined and NS3hel has been us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
111
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(124 citation statements)
references
References 40 publications
9
111
0
Order By: Relevance
“…Moreover, as the polynucleotide stimulator for ATP hydrolysis and the substrate for dsRNA unwinding were not derived from HCV RNA, NS3H is able to act on non-HCV RNA. These findings correspond with the observations from earlier reports [3,13,14]. mNS3H did not catalyze ATP hydrolysis (Fig.…”
Section: Resultssupporting
confidence: 93%
“…Moreover, as the polynucleotide stimulator for ATP hydrolysis and the substrate for dsRNA unwinding were not derived from HCV RNA, NS3H is able to act on non-HCV RNA. These findings correspond with the observations from earlier reports [3,13,14]. mNS3H did not catalyze ATP hydrolysis (Fig.…”
Section: Resultssupporting
confidence: 93%
“…5 and 6). Although the NS3 protease domain likely modulates nucleic acid substrate binding to increase duplex unwinding, it is not essential for the helicase activity (29,32). Thus, the fundamental mode of structural transitions involved in the motion of the HCV helicase is likely independent of the protease.…”
Section: Resultsmentioning
confidence: 99%
“…The NS3 protease domain, which is positioned to capture the C-terminal tail of the helicase in the structure of an engineered single-chain NS3-4A protein (28), may rearrange its interactions with NS3h to enhance RNA substrate binding (29,30). .…”
Section: Resultsmentioning
confidence: 99%
“…The isolated domains of NS3, i.e., the protease and helicase domains are functional on their own. It has been reported that in the full-length enzyme the NS3/4A protease enhances RNA binding and unwinding by the helicase and that also the helicase enhances protease activity (7,8). In the past decade, HCV NS3/4A protease has emerged as an important drug target for treatment of HCV infection.…”
mentioning
confidence: 99%